2008
DOI: 10.1038/ijo.2008.232
|View full text |Cite
|
Sign up to set email alerts
|

Leptin receptor signaling and the regulation of mammalian physiology

Abstract: The adipocyte-derived hormone, leptin, signals the status of body energy stores to the central nervous system to regulate appetite and energy expenditure. A specific long-form leptin receptor (LepRb), a type I cytokine receptor, mediates leptin action on LepRb-expressing neurons in the brain. Leptin binding to LepRb activates the associated Janus kinase-2 (Jak2) tyrosine kinase to promote the phosphorylation of Jak2 and three residues on LepRb; each of these sites mediates a distinct aspect of downstream LepRb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
136
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(144 citation statements)
references
References 66 publications
4
136
0
4
Order By: Relevance
“…Phosphorylation of each of these residues leads to the recruitment of a distinct set of downstream signaling molecules. By example, phosphorylated Tyr985 recruits the SH2-containing tyrosine phosphatase 2(SHP2), which presents the first step in the activation of the extracellular signal-regulated kinase (MAPK) cascade [19]. Additionally, phosphorylated Tyr985 also recruits SOCS3, a negative regulator of leptin action.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylation of each of these residues leads to the recruitment of a distinct set of downstream signaling molecules. By example, phosphorylated Tyr985 recruits the SH2-containing tyrosine phosphatase 2(SHP2), which presents the first step in the activation of the extracellular signal-regulated kinase (MAPK) cascade [19]. Additionally, phosphorylated Tyr985 also recruits SOCS3, a negative regulator of leptin action.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that hypothalamic leptin control of reproduction is regulated by signals independent of STAT3 signaling [20]. Finally, the phosphorylation of Tyr1077, the major phosphorylation site mediating leptin's effects on reproduction, promotes the recruitment and transcriptional activation of STAT5 [19] and is required for ongoing appropriate function of the female reproductive function [21].…”
Section: Introductionmentioning
confidence: 99%
“…This is not surprising as several nutritional factors regulate leptin and IGF1 production (8,9) . Both decline significantly in conditions of starvation (7) , through potentially independent mechanisms (10) .…”
mentioning
confidence: 95%
“…Renal biopsies were obtained from IgA-unassociated MsPGN in patients (ages, [18][19][20][21][22][23][24][25][26][27][28][29] at the 181 Hospital in Gulin, China, between March and September 2010. The diagnosis of IgA-unassociated MsPGN was confirmed through pathological diagnosis and the presence of other clinical evidence.…”
Section: Methodsmentioning
confidence: 99%